2015
DOI: 10.1007/s00253-015-6774-z
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-minute screening of antibiotic resistance genes in bacterial isolates with minimal sample preparation in static self-dispensing 64 and 384 assay cards

Abstract: In a clinical setting, molecular assays such as polymerase chain reaction offer a rapid means to infer or confirm identity and therapeutic decisions. Accordingly, a number of molecular assays targeting identity and antibiotic resistance (AR) genes have been developed; however, these methods can be technically complex and relatively expensive. Herein, we describe a diagnostic concept utilizing isothermal amplification technology with non-purified heat-lysed cells and self-dispensing cards for testing multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Alternative genotypic methods (detecting genes responsible for known mechanisms of resistance) are more rapid than culture-based approaches. [10] However, these resistance genes constitute only a fraction of all possible mechanisms of resistance, [11] and new forms of resistance evolve quickly. [12] Therefore, predicting resistance by analyzing a few known resistance genes is not a general solution.…”
mentioning
confidence: 99%
“…Alternative genotypic methods (detecting genes responsible for known mechanisms of resistance) are more rapid than culture-based approaches. [10] However, these resistance genes constitute only a fraction of all possible mechanisms of resistance, [11] and new forms of resistance evolve quickly. [12] Therefore, predicting resistance by analyzing a few known resistance genes is not a general solution.…”
mentioning
confidence: 99%
“…For some organisms and targets, direct LAMP amplification without DNA lyses may cause reduction in quantitative capacity or sensitivity. For example, previous studies with Staphylococcus aureus observed a 1 min difference between crudely lysed and non lysed cells (Kostic et al, 2015). Perhaps one of the greatest limitations of LAMP is increased possibility of contamination to subsequent reactions, due to the large concentration of generated amplicons.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, LAMP analysis is faster than qPCR because amplification can be accomplished without DNA extraction or using a crude lysate (Kostic et al, 2015; Modak et al, 2016). Previous studies demonstrated LAMP assays for quantification of Dehalococcoides spp.…”
Section: Introductionmentioning
confidence: 99%
“…Gene-Z performance has been demonstrated for many applications including bacterial pathogens important to water safety, human health, and assessing bioremediation performance in contaminated acquifers (Kostic et al 2015; Stedtfeld et al 2014). The work described here is its first demonstration for microRNA detection.…”
Section: Methodsmentioning
confidence: 99%
“…However, isothermal polymerases (e.g. Bst) are more robust and less impacted by inhibitory substrates compared to PCR polymerases (Kostic et al 2015; Stedtfeld et al 2014). Thus, an isothermal direct amplification approach has the potential to reduce analysis time and costs, without isolation and purification, and is therefore well suited for use outside of laboratories with specialized infrastructures (Njiru 2012).…”
Section: Introductionmentioning
confidence: 99%